Using Schema Modes for Case Conceptualization in Schema Therapy: An Applied Clinical Approach - Edwards, David John Arthur (Frontiers in Psychology, 2022)
This article is situated within the framework of schema therapy and offers a comprehensive and clinically useful list of schema modes that have been identified as being relevant to conceptualizing complex psychological problems, such as those posed by personality disorders, and, in particular, the way that those problems are perpetuated. Drawing on the schema therapy literature, as well as other literature including that of cognitive behavior therapy and metacognitive therapy, over eighty modes are identified altogether, categorized under the widely accepted broad headings of Healthy Adult, Child modes, Parent modes and coping modes which are, in turn, divided into Surrender, Detached/Avoidant, and Overcompensator. An additional category is included: Repetitive Unproductive Thinking. This draws attention to the recognition by metacognitive therapists that such covert behaviors play a significant role in amplifying distress and perpetuating a range of psychological problems and symptoms. In addition to the modes themselves, several concepts are defined that are directly relevant to working with modes in practice. These include: default modes, blended modes, mode suites and mode sequences. Attention is also drawn to the way in which Child modes may be hidden “backstage” behind coping modes, and to the dyadic relationship between Child modes and Parent modes. Also relevant to practice are: (1) the recognition that Critic voices may have different sources and this has implications for treatment, (2) the concept of complex modes in which several submodes work together, and (3) the fact that in imagery work and image of a child may not represent a Vulnerable Child, but a Coping Child. The modes and mode processes described are directly relevant to clinical practice and, in addition to being grounded in the literature, have grown out of and proved to be of practical use in conceptualizing my own cases, and in supervising the cases of other clinicians working within the schema therapy framework.